Risk Factor Profile of Amputation in Diabetic Foot Patients in Dr. Soetomo General Academic Hospital, Surabaya, from 2019 to 2020 - Adhibagio, Aria Damarjiwo; Soelistijo, Soebagijo Adi; Hakim, Arief Rakhman; Prasmono, Agung (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2024)
Highlights: Certain variables are known to be risk factors associated with the outcome of lower extremity amputation among diabetic foot patients. The patient population was observed to be slightly female-biased, with a high prevalence of older age, abnormally high blood sugar and HbA1c, and a history of nephropathy, dyslipidemia, and hypertension. Prior history of vascular diseases, prior amputation history, and heavy smoking were observed but not as prevalent.   Abstract Introduction: This study aimed to find the general distribution of certain variables as risk factors for lower extremity amputation among diabetic foot patients at the Inpatient Ward of the Department of Internal Medicine, Dr. Soetomo General Academic Hospital, Surabaya, from 2019 to 2020. Methods: This was a descriptive-retrospective study using data from medical records. The International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) version 26 was used to calculate the distribution. Results: The mean ± SD of age was 55.38 ± 7.503 years old and was slightly female-biased. The median (min-max) blood sugar level was 212.00 (85–446) mg/dL. Fifteen out of 16 patients had an HbA1c beyond 7.0%. The body mass index (BMI) of most patients was between normal and overweight, with a mean ± SD of 24.018 ± 4.1827. Fifteen percent of patients were smokers. Strokes were present in 3.9% of patients, cardiovascular diseases were present in 13.73% of patients, prior lower extremity amputation (LEA) history was present in 15.7% of patients, hypertension was present in 49% of patients, and dyslipidemia was present in 13 of 15 patients. The mean estimated glomerular filtration rate (eGFR) was 70.15 ± 34.498 mL/min/1.732. Conclusion: Older age, high blood sugar, high HbA1c levels, nephropathy, dyslipidemia, and hypertension had a high prevalence. Smoking, cardiovascular diseases, strokes, and prior amputation had a low prevalence. Gram-negative bacterial infection was observed in almost all reported patients. ABI results were either mostly not assessable or abnormally high. Most of the patients' Wagner gradings were in the worst category.